PENGARUH DISIPLIN KERJA, KOMPENSASI, MOTIVASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI - Mutia Reni; Ria Ariany; Roni Ekha Putera (Jurnal Muara Pendidikan, 2023)
The purpose of this study is to test and analyze how the influence of work discipline, compensation and motivation on employee productivity at SMKN 4 Padang both partially and simultaneously. This research is a form of associative research that has a form of variable relationship, namely causal relationships. While the approach used in this study is a quantitative approach. Collection techniques using questionnaires and data analysis using multiple linear regression and data processing using SPSS Version 25. The results of this study concluded that when viewed in the partial test of work discipline on work productivity gave a significant value of 0.000<0.05 with a B value of 0.289 which means that Ha was accepted and Ho was rejected. In the compensation variable, a significant value of 0.075>0.05 with a B value of 0.046, a significant value greater than 0.05 means that there is no compensation relationship to work productivity and it is concluded that Ha is rejected and Ho is accepted. Motivation significant value 0.000<0.05 with a contribution magnitude of 0.661 which means Ha is termed and Ho is rejected. If simultaneously tested, the significant value of the effect of work discipline, compensation and motivation on work pruductivity is 0.000 < 0.05 with a B value of 0.505, which means that there is a significant influence with Ho rejected and Ha received with a contribution value of 50.5%.